PENERAPAN METODE PEMBELAJARAN CS UNPLUGGED TEXT COMPRESSION UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI DASAR PEMROGRAMAN - Yusup Nurjaman, - (2011)
ICT learning is learning that requires a computer laboratory facilities are adequate, but according to Education Department data only 63% High School in West Java has a computer laboratory facilities. It means, there are so many high school in West Java has not computer laboratory, as a consequence the learning of ICT does not conveyed properly. Therefore the prevention of this problem are needed. Today has found a special ICT learning method that does not require a computer laboratory facilities, it's called CS Unplugged. This research intends to 1) To know the average result of learning student in the lesson using CS Unplugged learning methods an integrated PBL (Problem Based Learning) learning methods; 2) To know the average result of learning student in the lesson using CS Unplugged learning an integrated PBL (Problem Based Learning) methods better than student in the learning using conventional methods. This research method used CS Unplugged an integrated PBL (Problem Based Learning) with SMK Negeri 11 Bandung class X in academic year 2010/2011 as a sample and the research design used non equivalent control group pretes-postes design. The research instrument used were pretest and postest cognitive essay. From this research the result of learning an experimental class which given cs unplugged an integrated PBL learning is higher than control class which given conventional learning. From the test result using t-test, gained an increase learning result which given CS Unplugged an integrated PBL learning is better than the increase in learning result which the learning using the conventional methods.